Mitigating the implementation of SDGs program no. 13 in Indonesia: An overview of social dynamics and local wisdom - Negara, Anita Puspita; Ariza, Irena Sulistya; Nurjaya, Luh Asri Ningsih Widhi; Ubaidillah, Moh. Farich; Wijaya, Rama; Lestari, Vissia Poppy Puspita; Saputro, Erwan Adi; Sukirmiyadi; Nurherdiana, Silvana Dwi (E3S web of conferences, 2025)
This review critically examines the role of local wisdom in enhancing climate action as part of Sustainable Development Goal (SDG) No. 13 in Indonesia. The review explores key sectors including waste management, forest fire prevention, population dynamics, food security, and urban planning. Findings highlight that while local wisdom-based practices like “Tri Hita Karana” and customary land-use regulations are effective in mitigating environmental damage, scaling these approaches across diverse communities remains a challenge. Additionally, law enforcement against forest burning, coupled with traditional restorative justice, has shown promise in reducing environmental degradation. This review identifies significant gaps in policy integration, particularly in aligning local wisdom with national climate goals. Recommendations emphasize a more structured policy framework that incorporates traditional practices alongside modern mitigation strategies. This study aims to provide actionable insights for policymakers and stakeholders, offering a roadmap for integrating cultural heritage with climate action while also suggesting areas for future research in scaling up local initiatives.